Percutaneous needle aspiration of breast abscesses - Sarhan, Hamid H.; Ibraheem, Osama M. (Journal of the Faculty of Medicine Baghdad, 2012)
Background:Breast abscesses could be successfully treated by percutaneous aspiration of pus and irrigation of the cavity with saline solution. Objective:To assess the feasibility and effectiveness of percutaneous needle aspiration of breast abscesses under local anesthesia in the outpatient clinic. Patient and methods:A prospective study of forty three women with breast abscesses attended outpatient clinic at Tikrit teaching hospital and privit clinic for the period from January 2008 to January 2010.All patients had preliminary breast ultrasoundexamination. Percutaneous needle aspiration of pus under local anesthesia was done ,followed by systemic antibiotics. Repeated aspiration was carried out later when deemed necessary and follow up byultrasound was conducted. Results:Twenty three (53.4%) of patients obtained complete resolution (no focal collection) after one aspiration , 9 (21%) required two aspiration and 8 (18.6% )required more than two aspiration for cure (residual collection). In 3 ( 7% ) of patients, the treatment failed where symptoms not resolved after 3 days, with further pus collection despite aspiration and antibiotics , where surgical drainage were required. Conclusions:Percutaneous needle drainage of breast abscesses after preliminary breast US is feasible as a primary and definitive treatment for breast abscesses if complete or near complete drainage is achieved.